Women and Food Chains: The Gendered Politics of Food - Allen , Patricia; Sachs, Carolyn (The International Journal of Sociology of Agriculture and Food, 2007)
In nearly all societies women bear responsibility for the mental and manual labor of food provision, from field to table. Their involvement with food constructs who they are in the world—as family members, workers, and people—in deep, complex, and often contradictory ways. While food work often serves as a component of women’s identity, it also serves as a key factor in their exploitation, oppression, and, accordingly, their resistance. In this article we identify three domains that define women’s relationship to food—the material, the socio-cultural, and the corporeal. We find that, although the agrifood system is going through a period of rapid change, gender relations in the agrifood system remain surprisingly static. Through the lenses of material, socio-cultural, and corporeal, we briefly describe the state of contemporary gender relations in the American agrifood system, highlight some of the ways in which women are working to reconfigure social and economic conditions through food work. We find that, while women are engaged in significant and far-reaching efforts to change the system, few of these efforts focus specifically on improving gender relations. We briefly review scholarly contributions to our understanding of the gendered food system, concluding that a new field of study is needed that integrates theory and practice in the effort to understand and change gender relations in the agrifood system.